Teachers' perceptions of Restricted and Repetitive Behaviours (RRBs) in children with ASD: Attributions, confidence and emotional response. (June 2019) - Welsh, Patrick; Rodgers, Jacqui; Honey, Emma
Highlights: The study considers teachers' understanding of Restricted and Repetitive Behaviours in children with ASD. Differences in attributions exist as a result of different repetitive behaviours. School setting has an impact upon teachers' emotional response and confidence. Training around repetitive behaviours may be useful for some teachers. Abstract: Background: Restricted and Repetitive Behaviours (RRBs) are some of the most difficult behaviours to manage in children with Autism Spectrum Disorders (ASD). Although RRBs frequently occur in educational settings, we know little about the way in which teachers understand these behaviours. Aims: The study aimed to explore the attributions, emotional response and feelings of confidence held by teachers working in different educational settings when faced with RRBs. Methods and procedures: A single group survey design using behavioural vignettes was adopted in order to elicit teacher beliefs and ratings. Outcomes and results: Analysis indicated that there were differences in the attributions and confidence ratings held for different types of RRBs. Significant differences were also observed between teachers working in mainstream and specialist educational settings. Emotional response and confidence scores were often predictive of one another alongside factors related to teaching experience. Conclusion and implications: The findings indicate that teachers from mainstream schools potentially hold less helpful beliefs in response to RRBs and therefore are a professional group who may benefit the most from additional support and training. Further research could consider conducting a qualitative exploration of why teachers hold certain beliefs about RRBs and/or sampling those who are less experienced in working with children with ASD.